Impact of two different types of heat stress on chloroplast movement and fluorescence signal of tobacco leaves - Frolec, Jirí; Rebícek, Jirí; Lazár, Dusan; Naus, Jan (Plant cell reports, 2010)
Although the chloroplast movement can be strongly affected by ambient temperature, the information about chloroplast movement especially related to high temperatures is scarce. For detailed investigation of the effects of heat stress (HS) on tobacco leaves (Nicotiana tabacum L. cv. Samsun), we used two different HS treatments in dark with wide range of elevated temperatures (25-45 degrees C). The leaf segments were either linearly heated in water bath at heating rate of 2 degrees C min(-1) from room temperature up to maximal temperature (T (m)) and then linearly cooled down to 25 degrees C or incubated for 5 min in water bath at the same T (m) followed by 5 min incubation at 25 degrees C (T-jump). The changes in light-induced chloroplast movement caused by the HS pretreatment were detected after the particular heating regime at 25 degrees C using a method of time-dependent collimated transmittance (CT) and compared with the chlorophyll O-J-I-P fluorescence rise (FLR) measurements. The inhibition of chloroplast movement started at about 40 degrees C while the fluorescence parameters responded generally at higher T (m). This difference in sensitivity of CT and FLR was higher for the T-jump than for the linear HS indicating importance of applied heating regime. A possible influence of chloroplast movement on the FLR measurement and a physiological role of the HS-impaired chloroplast movement are discussed.
Keywords: vysoká teplota; Chloroplasts; světlo; Temperature; Photosynthesis; Plant Leaves; Phototropism; fototropismus; Light; Photic Stimulation; Chlorophyll; světelná stimulace; fotosyntéza; tabák; teplota; Cell Movement; Fluorescence; Hot Temperature; pohyb buněk; chlorofyl; fyziologický stres; fotochemie; Photochemistry; chloroplasty; Nicotiana; listy rostlin; Stress, Physiological; fluorescence